Representing the Marginalized Other: The Swedish Hip-hop Group Advance Patrol - Lindholm, Susan (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2014)
Hip-hop artists are often perceived as societal critics who speak for, or represent a marginalized other, while at the same time re-presenting or staging themselves as individual artists. This article sets out to provide a more detailed account of the representation of such a marginalized other in Swedish Hip-hop by tracing the ways in which representation – as both speaking for and staging – is connected to the marginalized other in the lyrics of the Malmö-based Hip-hop group Advance Patrol. In their lyrics, Advance Patrol not only stage themselves as artists who speak for a marginalized other and artists who distance themselves from such representations by creating an externalized other. Their lyrics also stage them as what will be called a transnational other in-between Chile and Sweden and thereby connect them with a migration history in-between Chile and Sweden. It argues that the representations in their lyrics between 2003 and 2006 shift – between criticizing the logic of ’we’ against ’them’ that creates the marginalized other, and an affirmation of such marginalization. These shifting representations thus represent it as a concept that can never be fully assimilated into a dominant hegemonic structure, a concept that resists appropriation into forms of solidarity that claim to know or speak its ’truth’.